2022
DOI: 10.1002/ejlt.202100149
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Aspects of Vegetable Oils: Refined or Unrefined?

Abstract: Nowadays, increase in a health-conscious population, interest in the nutritional properties and bioactive components of foods has also increased. Vegetable oils can be consumed in both virgin and refined forms, but there is a growing interest in the consumption of virgin oils as functional foods. Refining includes the elimination of unwanted components while maintaining essential elements. However, due to severe conditions such as high temperatures and harsh chemicals of the refining process, removal of desira… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 68 publications
(147 reference statements)
0
4
0
Order By: Relevance
“…Generally, there is a shortage in the daily diet in the level of n‐3 fatty acids compared to the n‐6 essential fatty acids, which can initiate and cause many disorders and diseases (Hashempour‐Baltork et al., 2018 ; Tang et al., 2021 ). Therefore, consuming and using vegetable oils rich in n‐3 fatty acids are necessary and recommended in the daily diet (Hashempour‐Baltork et al., 2022 ). On the other hand, vegetable oils such as flaxseeds with high content of unsaturated fatty acids are less stable and need unique preservation methods such as storage at the very low level of temperature and in dark condition and applying antioxidants.…”
Section: Resultsmentioning
confidence: 99%
“…Generally, there is a shortage in the daily diet in the level of n‐3 fatty acids compared to the n‐6 essential fatty acids, which can initiate and cause many disorders and diseases (Hashempour‐Baltork et al., 2018 ; Tang et al., 2021 ). Therefore, consuming and using vegetable oils rich in n‐3 fatty acids are necessary and recommended in the daily diet (Hashempour‐Baltork et al., 2022 ). On the other hand, vegetable oils such as flaxseeds with high content of unsaturated fatty acids are less stable and need unique preservation methods such as storage at the very low level of temperature and in dark condition and applying antioxidants.…”
Section: Resultsmentioning
confidence: 99%
“…A higher level of saturated fatty acids has adverse effects on the nutritional properties of the fats and oils, but can increase the oxidative stability of these products. Therefore, a balanced ratio of saturated and unsaturated acids, particularly essential fatty acids, is necessary to achieve a suitable stability and optimal nutritional properties [41]. Sesame seed oil exhibited a high content of linoleic acid (18:2) as an omega-6 fatty acid, but it has a very low level of fatty linolenic acid (18:3), which is an omega-3 essential fatty acid (Table 5).…”
Section: Fatty Acid Compositionmentioning
confidence: 99%
“…Nehchiri et al [3] found that the UV-light barrier ability of the alginate film was significantly improved when the film was coated with sunflower or linseed oil. POs typically contain various polyphenolic compounds that can act as UV light blockers and improve the UV protection properties of the film [47,49]. Therefore, they can be considered as potential UV barrier ingredients for application in food packaging.…”
Section: Ultraviolet Light Transmittancementioning
confidence: 99%